Implementation of Mentoring Methods in Improving the Professionalism of School Principals in Elementary Schools at Tapung Hilir Districts of Kampar - Yatimah, Yatimah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the low professionalism of school principals in elementary schools in Tapung Hilir Districts of Kampar. Based on temporary observations, it is generally seen that school principals, especially in elementary schools in Tapung Hilir Districts of Kampar, do not meet the qualifications of professional principals. It indicates that 1) the appointment of school principals was not transparent, 2) the low mental level of school principals was characterized by a lack of motivation and enthusiasm in carrying out their duties, 3) principals often came late, and 4) the principal's insight did not appear to be broad. The type of research is School Action Research with a Kemmis and Mc model research design. Taggart is a spiral from one cycle to the next. The research population involved 11 school principals in SD in Tapung Hilir Districts of Kampar and the entire population was used as a sample. Based on the description of data processing and discussion, it was concluded that the professionalism of school principals in cycle I was 71.8% with the good category and in cycle II it increased to 83.9% with the good category. This means that the mentoring method is able to increase the professionalism of school principals in elementary schools in Tapung Hilir Districts of Kampar and is said to be successful.